The Clinical Case of Total Effective Removal of a Craniovertebral Junction Tumor (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The prevalence of meningiomas is due to their high incidence. According to the US Central Brain Tumor Registry, meningiomas account for 35.5% of the overall incidence of primary CNS tumors, which is 20 per 100,000 population per year. In people 35 years and older, meningioma is the most common CNS tumor. In people 85 years and older, the incidence of meningiomas reaches 46 per 100,000 population per year or more. The incidence rate of spinal meningiomas is three times higher than that of gliomas [1,2,5]. Spinal meningiomas are often diagnosed in the elderly. Thus, patients over 60 years of age account for 60% of the total number of primary spinal tumors. Such tumors are mainly diagnosed in women. Most meningiomas are localized in the thoracic spine, and are extremely rare in the lumbar spine [3,4]. The most typical localization of the tumor relative to the spinal cord is ventrolateral. The problem of timely and correct diagnosis is relevant. Most patients are hospitalized in a neurosurgical hospital with severe neurological deficit. The main goal of the operation is to improve spinal cord function and radically remove the tumor. The widespread use of microsurgical techniques in neurosurgery has made it possible to radically remove spinal meningiomas in 92–97% of cases, while the mortality rate does not exceed 2–3%. Positive dynamics were noted in 80% of observations [6,7,8].